Le stereotype comme la manifestation des particularites culturelles - Seidikenova, Almash; Bakitov, Aitkali (International relations and international law Journal, 2018)
The concept «stereotype» is studied in different branches of science. This concept is considered in branches of science as the philosophy, psycholinguistics, sociology, psychology, ethnography, cultural science, etc. Representatives of the above-stated branches of sciences consider and express opinion on the concept «stereotype» and do classification of a stereotype according to requirements of the branch. Having analyzed the concept «stereotype» of various sciences, it is possible to note that formations of stereotypes are the cornerstone cognitive processes. Stereotypes are acquired in the course of socialization and an inculturation, also special place in formation of stereotypes borrow mass media. Stereotypes perform a number of cognitive functions such as schematization and simplifications, formations and storages of group ideology and other cogitative functions. Every person has individual personal experience, a special form of perception of the world around on the basis of which in his head the socalled «picture of the world» including an objective part and value judgment of reality an individual is created. The stereotype is an integral part of this picture. Within this article we consider ethnic stereotypes, stereotypes of thinking and linguistic stereotypes of the Kazakh and French languages, analyzing scientific views of scientific different branches concerning the concept «stereotype».